Exercise and training in women, part I: Influence of gender on exercise and training responses - Shephard, R. J. (Canadian Journal of Applied Physiology, 2000)
Exercise and training responses in women are briefly reviewed. Part I of the paper considers the influence of gender on such responses. The average woman has a smaller inherent aerobic power and less muscular strength than a man, reflecting sociocultural influences, physical size, body composition, and hormonal milieu. Nevertheless, the best-trained women can out-perform sedentary men. The handicap of the average woman is offset by a lighter body mass and a tendency to metabolize fat rather than carbohydrate during exercise. A lack of anabolic hormones may limit training increases of muscle bulk in the female. A low initial fitness may enhance the scope for training tolerance, but it also limits tolerance of conditioning. Nevertheless, women seem less vulnerable than men to exercise-induced sudden death and overtraining.